2009
DOI: 10.1038/emboj.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation defects activate filamentous growth Kss1 MAPK and inhibit osmoregulatory Hog1 MAPK

Abstract: The yeast filamentous growth (FG) MAP kinase (MAPK) pathway is activated under poor nutritional conditions. We found that the FG‐specific Kss1 MAPK is activated by a combination of an O‐glycosylation defect caused by disruption of the gene encoding the protein O‐mannosyltransferase Pmt4, and an N‐glycosylation defect induced by tunicamycin. The O‐glycosylated membrane proteins Msb2 and Opy2 are both essential for activating the FG MAPK pathway, but only defective glycosylation of Msb2 activates the FG MAPK pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 55 publications
9
101
0
6
Order By: Relevance
“…The Opy2 G207D and Opy2 C30Y proteins were also defective for HOG pathway signaling, based on the saltdependent phosphorylation of the MAPK that functions in the HOG pathway, Hog1 ( Figure S2C). Together, our results support and extend the conclusion put forward in Yang et al (2009) that Opy2 is a general adaptor for the HOG and filamentous growth pathways that functions by plasmamembrane recruitment of Ste50.…”
Section: Opy2 Regulates the Filamentous Growth Pathway By Plasma-membsupporting
confidence: 90%
See 2 more Smart Citations
“…The Opy2 G207D and Opy2 C30Y proteins were also defective for HOG pathway signaling, based on the saltdependent phosphorylation of the MAPK that functions in the HOG pathway, Hog1 ( Figure S2C). Together, our results support and extend the conclusion put forward in Yang et al (2009) that Opy2 is a general adaptor for the HOG and filamentous growth pathways that functions by plasmamembrane recruitment of Ste50.…”
Section: Opy2 Regulates the Filamentous Growth Pathway By Plasma-membsupporting
confidence: 90%
“…Opy2 functions in the HOG pathway (Wu et al 2006;Ekiel et al 2009;Yang et al 2009;Yamamoto et al 2010;Cappell and Dohlman 2011) and may also regulate the filamentous growth pathway (Yang et al 2009;Yamamoto et al 2010), although this possibility has not been extensively explored (Wu et al 2006;Chen and Thorner 2007). To determine whether Opy2 regulates the filamentous growth pathway, the OPY2 gene was deleted in strains of the filamentous ( P 1278b) background (Liu et al 1996).…”
Section: Opy2 Regulates the Filamentous Growth Pathway By Plasma-membmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the deletion of pmt4 does not affect cell cycle progression, mating, or polar growth, it seems unlikely that these proteins are responsible for the phenotypes we observe in U. maydis, although we are currently working to test this experimentally. Sc Fus1p, Sc Opy2p, and Sc Msb2p, components of the yeast filamentous growth mitogen-activated protein kinase pathway, have recently been described as additional PMT4 targets (Yang et al, 2009). We found that U. maydis contains only some elements of the yeast filamentous growth mitogen-activated protein kinase pathway.…”
Section: Effects Of Protein O-mannosylation On Cell Wall Integrity Anmentioning
confidence: 62%
“…Pmt4--initiated O--mannosylation is also necessary for cell surface delivery of Fus1, because the unglycosylated protein accumulates in the late Golgi ). Defects in Pmt4--dependent O--glycosylation of Msb2 (as well as N--glycosyation) of osmosensor Msb2 lead to activation of the filamentous growth signaling pathway (Yang et al 2009). In this case, underglycosylation may unmask a domain that normally is exposed and makes interactions when the signaling pathway is activated legitimately.…”
Section: Pmt Mutants Show That O--mannosylation Can Be Important For mentioning
confidence: 99%